Upaya Meningkatkan Hasil Belajar Siswa dalam Pembelajaran IPS Melalui Metode Ceramah di Kelas VI SD S Tiga Hati - Aidil Fahmi Saragih (Dharmas Education Journal (DE_Journal), 2022)
The main task of the teacher is to help students in terms of learning. In the process of teaching and learning teachers must provide courses to solve problems in the classroom, evaluating student learning, both before pre, middle and after class. A teacher must have high professional ability to carry out his or her role. Research has been conducted on "Efforts to Improve Student Learning Outcomes in IPS Learning Through Lecture Methods in Class VI SD S Tiga Hati". The purpose of this research is to improve student learning outcomes in IPS learning by using lecture methods. Quantitative data is obtained from observation. Interviews and homework. Qualitative analysis of data is data reduction, data presentation, data verivikation and quantitative analysis by using formulas to determine individual and classical absorption, degree of completion of classical learning, and average percentage. The results obtained are that students experience progress in their learning outcomes, compared to previous results still 26,6% of students who completed that 8 of the 30 students, in cycle I experienced an increase 30% from the initial activity to 56,6% that is 17 students who completed and in cycle II increased again that 26,7% to 83,3% where there is 25 Students who graduated from 30 students.